Lean Startup Approach for Developing Information System of Research and Community Service (SIRIP) - Chrystia Aji Putra; Sugiarto (Future Science)
Development of this Information System of Research and Community Service (SIRIP) program is expected to grow outside Universitas Pembangunan Nasional “Veteran” Surabaya, East Java, Indonesia. SIRIP is a solution system for all universities in order to support their “Tridharma Perguruan Tinggi” at point B and C, which are each lecturer are obliged to conduct research and community services each year. Research Institution and Community Service of Universitas Pembangunan Nasional “Veteran” Surabaya, East Java, Indonesia has been applied, which creates maximum result and helps Institution of Research and Community Service officer to conduct data entry and monitoring of community service activities. Using Lean Startup Approach, it is expected that this SIRIP can be a startup pioneer on SIMLITABMAS field of study by Institute Internal version. So that university will no longer have difficulties to report to the central about their proposed research data and community service that has been conducted by the internal campus.